A Case Study of Math Anxiety in High School Students: Assessment, Dynamics, and Intervention - Ilham, Muhammad; Habibi, Mhmd; Ropawandi, Doni (Edumatika, 2025)
Mathematics anxiety is a pervasive issue among adolescents, often impairing academic performance and emotional well-being. This study investigates the psychological profile of an Indonesian high school student experiencing mathematics anxiety following an academic transition from the UK to Indonesia and evaluates the effectiveness of a Cognitive Behavioral Therapy (CBT) intervention in reducing her anxiety. This research used a single-case qualitative design; data were gathered through psychological assessments (IST, DAT A5, SSCT, graphic tests), structured interviews with the participant, parents, and teachers, and behavioral observations. A five-session CBT intervention focusing on cognitive restructuring was conducted over two weeks. The assessment revealed average intellectual ability but significant cognitive distortions, physiological symptoms, and avoidance behaviors related to mathematics. Post-intervention findings demonstrated notable improvements in cognitive beliefs, emotional regulation, class participation, and help-seeking behavior. The participant, her teacher, and her mother all reported reduced anxiety and improved academic coping. The findings support the use of CBT as an effective and culturally adaptable approach for addressing mathematics anxiety in adolescents. The study emphasizes the role of cognitive patterns, emotional processes, and environmental influences in the development and resolution of academic anxiety. These insights are relevant for educators, school psychologists, and mental health professionals working in diverse educational settings. However, due to its single-case design and reliance on self-reported outcomes, the generalizability of the findings is limited and further research with larger and more diverse samples is recommended.